Comparative analysis of IL-8 and CXCL-1 production by normal and cancer stromal fibroblasts - Szabo, P; Valach, J; Smetana, K; Dvořánková, B (Folia biologica, 2013)
It has been shown that fibroblasts within the stroma of malignant tumours can affect the tumour's biological character, influencing such properties as local aggressiveness and metastasis potential. This influence is asserted via paracrine secretion of multiple cell factors, including chemokines. This study demonstrates that both normal keratinocytes and cancer cells can stimulate the secretion of chemokines IL-8 and CXCL-1 from normal dermal fibroblasts and stromal fibroblasts from squamous cell carcinoma. The effect of epithelia on normal fibroblasts leads to a transient secretory change, in contrast to stromal fibroblasts which generate a more prolonged one. This observation demonstrates that stimulated expression of both IL-8 and CXCL-1 is not specific to cancer, supporting the hypothesis that similar mechanisms exist between wound healing and oncogenesis. It also shows that stromal fibroblasts isolated from a tumour have significantly different features from normal fibroblasts.
Keywords: nádorové proteiny; Hypopharyngeal Neoplasms; nádory hypofaryngu; fibroblasty; buňky stromatu; Up-Regulation; škára; Fibroblasts; Interleukin-8; Skin Neoplasms; Culture Media, Conditioned; chemokin CXCL1; upregulace; Stromal Cells; Keratinocytes; kultivační média speciální; Dermis; Coculture Techniques; kultivované buňky; keratinocyty; lidé; Wound Healing; Humans; Chemokine CXCL1; interleukin-8; kokultivační techniky; Neoplasm Proteins; rychlost sekrece; nádory kůže; Cells, Cultured; Secretory Rate; spinocelulární karcinom; Carcinoma, Squamous Cell; hojení ran